Real-time obscene scene nudity detection and blurring in a video clip - Rizwana, Jesima; Hasan, Md. Fahim; Hossain, Motakabbir; Zahangir, Kaniz Ferdous Binte; Prothoma, Humaira Mir (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.